Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 2 - Equations, Inequalities, and Problem Solving - 2.2 Using the Principles Together - 2.2 Exercise Set - Page 94: 43



Work Step by Step

By combining like terms and by using the properties of equality, the solution to the given equation, $ 6x+3=2x+3 $, is \begin{array}{l}\require{cancel} 6x-2x=+3-3 \\\\ 4x=0 \\\\ x=\dfrac{0}{4} \\\\ x=0 .\end{array} Checking: \begin{array}{l}\require{cancel} 6(0)+3=2(0)+3 \\\\ 3=3 \text{ (TRUE)} .\end{array} Hence, $ x=0 $.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.